2018
DOI: 10.1002/pon.4660
|View full text |Cite
|
Sign up to set email alerts
|

Expecting the worst? The relationship between retrospective and prospective appraisals of illness on quality of life in prostate cancer survivors

Abstract: Results suggest both retrospective and prospective appraisals are independently related to QOL in prostate cancer. Providing survivors with more information about possible adverse effects of treatment, as well as providing appropriate information regarding future disease progression, may improve QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Specifically, time since diagnosis (Boehmer et al, 2016;Maguire et al, 2017) was significantly associated with higher FCR, whilst which contrasts with the cancer survivorship literature (Crist and Grunfeld, 2013;Koch et al, 2013;Simard et al, 2013). Four studies found that treatment modality was significantly associated with FCR, which is consistent with the cancer patient and survivorship literature that indicates that different treatment approaches are significantly associated with FCR (Yang et al, 2017a,b;Maguire et al, 2018). Patients who have had chemotherapy or radiotherapy are likely to experience side effects, and an increased number of hospital trips and inpatient episodes, which may contribute to psychological morbidity (Denlinger and Barsevick, 2009).…”
Section: Discussionmentioning
confidence: 73%
“…Specifically, time since diagnosis (Boehmer et al, 2016;Maguire et al, 2017) was significantly associated with higher FCR, whilst which contrasts with the cancer survivorship literature (Crist and Grunfeld, 2013;Koch et al, 2013;Simard et al, 2013). Four studies found that treatment modality was significantly associated with FCR, which is consistent with the cancer patient and survivorship literature that indicates that different treatment approaches are significantly associated with FCR (Yang et al, 2017a,b;Maguire et al, 2018). Patients who have had chemotherapy or radiotherapy are likely to experience side effects, and an increased number of hospital trips and inpatient episodes, which may contribute to psychological morbidity (Denlinger and Barsevick, 2009).…”
Section: Discussionmentioning
confidence: 73%
“…Less attention has been paid to psychological appraisals made by the caregiver and how these might separately impact on well-being, regardless of the care situation. It is known that appraisals of illness can impact well-being in those who are suffering from chronic health conditions [20][21][22][23]. The same is likely to be the case for caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from perceptions of support, a range of other psychological appraisals may play an important role in maintaining well-being in those with chronic illness (De Ridder et al, 2008; Maguire et al, 2018). For example, optimism has been demonstrated to be highly predictive of quality of life, with optimistic individuals more likely to report higher well-being (Karademas, 2006; Scheier et al, 2001) and better health outcomes (DuBois et al, 2015).…”
Section: Introductionmentioning
confidence: 99%